Effects of high velocity oxy fuel thermal spray coating on mechanical and tribological properties of materials–A review. (2020) - Padmavathi, G.; Sarada, B.N.; Shanmuganathan, S.P.; Padmini, B.V.; Mohan, N.
Abstract: Chromium has excellent wear and corrosion properties with good lubrication and chemical resistance mainly used for decorative and practical applications. Nevertheless, the necessity to recognize replacements or to enhance the mechanical characteristics of chromium electroplating is of paramount importance mainly to overcome the environmental pollution and to enhance the fatigue strength of the substrate. The main reason for chromium coatings is to improve wear and corrosion properties of the component. But the main byproduct of this process is Cr + 6 (hexavalent chromium), that is hazardous to wellbeing of the surroundings. High Velocity Oxygen Fuel thermal spray coating (HVOF) is developed as an exceptional replacement for conventional hard chromium electroplating process. HVOF coatings possess improved hardness, wear and fatigue resistance in contrast to hard chromium coatings. An attempt has been made to conduct a survey to analyze the result of mechanical and tribological characteristics of HVOF coatings.